2021
DOI: 10.1080/02705060.2020.1853624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the nutrient status and forage quality of the hippo grass (Vossia cuspidata (Roxb.) Griff.) along Ismailia canal, Egypt

Abstract: The present study aims at investigating the potential of the hippo grass for sequestering inorganic and organic nutrients in its biomass, in addition to its forage quality along Ismailia Canal, Egypt. Eight sites including 6 polluted and 2 unpolluted were selected for a seasonal plant, water and sediment investigations. The nutrients and nutritional value of the plant tissues were estimated. The highest aboveground biomass was recorded during summer, while the lowest was in winter. The plant had the highest co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…Our research found that summer is the best time to harvest C. alopecuroides for greatest removal of Na, K, and N, while spring is best for removal of Ca, P, and Mg from eutrophic water bodies. This conclusion is consistent with the findings of Galal et al [41,43], who attributed it to the greatest nutrient accumulation (particularly N and P) linked with maximal plant biomass throughout the summer. Furthermore, Eid et al [29] identified spring as the best period to harvest P. australis with the maximum nutrient content and biomass to address Lake Burullus eutrophication in Egypt.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our research found that summer is the best time to harvest C. alopecuroides for greatest removal of Na, K, and N, while spring is best for removal of Ca, P, and Mg from eutrophic water bodies. This conclusion is consistent with the findings of Galal et al [41,43], who attributed it to the greatest nutrient accumulation (particularly N and P) linked with maximal plant biomass throughout the summer. Furthermore, Eid et al [29] identified spring as the best period to harvest P. australis with the maximum nutrient content and biomass to address Lake Burullus eutrophication in Egypt.…”
Section: Discussionsupporting
confidence: 93%
“…There is a large seasonal fluctuation in the inorganic nutrients among C. alopecuroides tissues and between unpolluted and polluted regions. This finding is consistent with Klaus et al [49] and Galal et al [41], who determined that plant size and growing season are the primary causes of nutritional variance. The below-ground regions of polluted water bodies contributed the most Na and K concentrations during the summer, and the least N and P concentrations during the winter.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous chemical analysis verified and estimated the contents of Na, K, N, Mg, P, Ca, ether, crude fibres, proteins, ash, and carbohydrates with seasonable variations in the aboveground leaves and stem, and in the belowground roots and rhizome of Vossia cuspidata 65 . Figure 1 A,B show the FTIR of the PL and PR biomasses before “pristine” and after getting loaded with the MB dye.…”
Section: Resultsmentioning
confidence: 89%